Measurement of the 229 Th isomer energy with a magnetic microcalorimeter - Sikorsky, Tomas; Geist, Jeschua; Hengstler, Daniel; Kempf, Sebastian; Gastaldo, Loredana; Enss, Christian; Fleischmann, Andreas (Physical review letters, 2020)
We present a measurement of the low-energy (0-60 keV) γ-ray spectrum produced in the α decay of 233U using a dedicated cryogenic magnetic microcalorimeter. The energy resolution of ∼10 eV, together with exceptional gain linearity, allows us to determine the energy of the low-lying isomeric state in 229Th using four complementary evaluation schemes. The most precise scheme determines the 229Th isomer energy to be 8.10(17) eV, corresponding to 153.1(32) nm, superseding in precision previous values based on γ spectroscopy, and agreeing with a recent measurement based on internal conversion electrons. We also measure branching ratios of the relevant excited states to be b29=9.3(6)% and b42<0.7%.